Postoperative effects of neuromuscular exercise prior to hip or knee arthroplasty: a randomised controlled trial. Issue 6 (9th May 2013) - Villadsen, Allan; Overgaard, Søren; Holsgaard-Larsen, Anders; Christensen, Robin; Roos, Ewa M
Abstract : Objective: To investigate the postoperative efficacy of a supervised programme of neuromuscular exercise prior to hip or knee arthroplasty. Methods: In this assessor-blinded randomised controlled trial, we included 165 patients scheduled for hip or knee arthroplasty due to severe osteoarthritis (OA). An 8-week preoperative neuromuscular supervised exercise programme was delivered twice a week for 1 h as adjunct treatment to the standard arthroplasty procedure and compared with the standard arthroplasty procedure alone. The primary outcome was self-reported physical function measured on the activities of daily living (ADL) subscale in the Hip disability and Osteoarthritis Outcome Score (HOOS) and the Knee injury and Osteoarthritis Outcome Score (KOOS) questionnaires for patients with hip and knee OA, respectively. Primary endpoint was 3 months after surgery. Results: 165 patients randomised to the two groups were on average 67±8 years, 84 (51%) had hip OA and 92 (56%) were women. 153 patients (93%) underwent planned surgery and were evaluated postoperatively. There was no statistically significant difference in effects between hip or knee patients (p=0.7370). Three months postoperatively, no difference was found between groups for ADL (4.4, 95% CI −0.8 to 9.5) or pain (4.5, 95% CI −0.8 to 9.9). However, there was a statistically significant difference indicating an effect of exercise over the entire period (baseline to 3-months postoperatively) (p=0.0029). Conclusions: Eight weeks of supervised neuromuscular exercise prior to total joint arthroplasty (TJA) of the hip or knee did not confer additional benefits 3 months postoperatively compared with TJA alone. However, the intervention group experienced a statistically significant short-term benefit in ADL and pain, suggesting an earlier onset of postoperative recovery. Trial registration: ClinicalTrials NCT01003756 .